ChemInform Abstract: Tetrahydroxydiboron‐Mediated Palladium‐Catalyzed Transfer Hydrogenation and Deuteriation of Alkenes and Alkynes Using Water as the Stoichiometric H or D Atom Donor. Issue 45 (October 2016) - Cummings, Steven P.; Le, Thanh‐Ngoc; Fernandez, Gilberto E.; Quiambao, Lorenzo G.; Stokes, Benjamin J.
Abstract: The hydrogenation of alkenes and alkynes to the corresponding saturated hydrocarbons is achieved in high yields using tetrahydroxydiboron B2 (OH)4 as the reagent and water as hydrogen source.